2011
DOI: 10.3400/avd.cr.10.01037
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Arteriovenous Fistula Associated with Iinfrarenal Aorto-iliac Aneurysm: Report of Two Contrasting Cases

Abstract: We present two cases of arteriovenous fistulas associated with aneurysms of the infrarenal aorta or common iliac artery. A definitive diagnosis is sometimes difficult given the varied and unclear presentation. However, with the correct preoperative diagnosis, mortality can be reduced. Both cases, being reported here, were diagnosed preoperatively and underwent alternate surgical repairs. One case was treated by aortic exclusion, whereas the second case was treated by primary closure of the fistula. Repair tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(23 reference statements)
0
2
0
Order By: Relevance
“… 2 ) Some studies have reported an AVF located in the anterior wall of veins. 3 , 4 ) This case is quite rare in that the AVF associated with the aneurysm was located in the posterior wall of the CIV. The fistula was not directly visible in this case.…”
Section: Discussionmentioning
confidence: 90%
“… 2 ) Some studies have reported an AVF located in the anterior wall of veins. 3 , 4 ) This case is quite rare in that the AVF associated with the aneurysm was located in the posterior wall of the CIV. The fistula was not directly visible in this case.…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, the traditional surgical operative risk based on aneurysmal excision, fistula closure and graft inclusion remained high for decades, with a mortality rate as high as 50 percent [Gilling-Smith 1991;Maeda 2007]. As an alternative, the exclusion techniqueoriginally developed for infra-renal aortic aneurysms [Corson 1987] -which includes division of the aorta with suture closure of the proximal and distal aspects of the aneurysm, and bypass of the excluded segment has also been utilized in the context of aortoiliac aneurysms with aortocaval fistula when fistula itself could not be closed during surgery [Woolley 1995;Batt 1996;Kondo 2011]. In recent years, evolving endovascular techniques have been utilized in this clinical entity with no perioperative mortality and a technical success rate of 96 percent [Antoniou 2009].…”
Section: Introductionmentioning
confidence: 99%